ANALISIS PREDIKSI KEBANGKRUTAN DENGAN MODEL ALTMAN, SPRINGATE, GROVER & ZMIJEWSKI PADA INDUSTRI MANUFAKTUR DI BEI - Wijaya, Errin Yani (Jurnal Tepak Manajemen Bisnis, 2016)
This research aims to determine inaccuracies some of bankruptcy prediction models which are Altman, Springate, Grover, and Zmijewski in predicting bankruptcy in manufacturing industry in Indonesia Stock Exchange(IDX).This study was conducted on 140 companies listed in the Indonesia Stock Exchange in 2013 using census method. The analytical tool is descriptive analysis.The results showed the entire bankruptcy prediction model failed in predicting the bankruptcy of the manufacturing industry in Indonesia as evidenced by its low percentage compared to the actual bankruptcy prediction has been done before.